2008
DOI: 10.1007/s10278-008-9145-9
|View full text |Cite
|
Sign up to set email alerts
|

Collecting 48,000 CT Exams for the Lung Screening Study of the National Lung Screening Trial

Abstract: From 2002-2004, the Lung Screening Study (LSS) of the National Lung Screening Trial (NLST) enrolled 34,614 participants, aged 55-74 years, at increased risk for lung cancer due to heavy cigarette smoking. Participants, randomized to standard chest X-ray (CXR) or computed tomography (CT) arms at ten screening centers, received up to three imaging screens for lung cancer at annual intervals. Participant medical histories and radiologist-interpreted screening results were transmitted to the LSS coordinating cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The LSS confirmed LDCT's higher lung cancer detection rate compared with CXR: 1.8 vs 0.5% at baseline, and 2.4 vs 1.3% at the first year repeat. On the basis of the success of LSS, the National Cancer Institute, in collaboration with the American College of Radiology Imaging Network, launched the National Lung Screening Trial, which represents the largest randomised controlled trial comparing LDCT with CXR, with lung cancer mortality as the end point (Clark et al, 2008). More than 53 000 participants were enrolled from over 30 centres across the United States.…”
Section: Randomised Trials With Low-dose Spiral Ctmentioning
confidence: 99%
“…The LSS confirmed LDCT's higher lung cancer detection rate compared with CXR: 1.8 vs 0.5% at baseline, and 2.4 vs 1.3% at the first year repeat. On the basis of the success of LSS, the National Cancer Institute, in collaboration with the American College of Radiology Imaging Network, launched the National Lung Screening Trial, which represents the largest randomised controlled trial comparing LDCT with CXR, with lung cancer mortality as the end point (Clark et al, 2008). More than 53 000 participants were enrolled from over 30 centres across the United States.…”
Section: Randomised Trials With Low-dose Spiral Ctmentioning
confidence: 99%
“…WUSTL has served as an imaging core in multi-center clinical trials, e.g., the Silent Cerebral Infarct Transfusion Trial (SITT) (∼1,000 patients; 1,552 examinations; 850,000 images) [17] and the CT Image Library for the Lung Screening Study of the National Lung Screening Trial (NLST) (17,309 patients with serial CT screens; 48,723 CT examinations; 12 million images) [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, data for the prognosis of lung cancer cases identified on CT screening are limited [4][5][6] and the effect of this screening procedure on mortality remains inconclusive. While several randomized controlled trials are ongoing [7][8][9][10], results of previous analyses [11][12][13] have not supported an effect of CT-based screening in lowering lung cancer mortality. Recently, however, the National Lung Screening Trial (NLST), a randomized trial targeted for current and former heavy smokers, found a 20% reduction in lung cancer death among participants screened with low-dose helical CT compared to participants screened with chest X-ray [14].…”
Section: Introductionmentioning
confidence: 88%